Evaluation of a satellite telemetry system for monitoring movements of caribou - Curatolo, James A. (Rangifer, 1986)
A cow caribou from the Central Arctic Herd was collared with a satellite-monitored radio transmitter in the Kuparuk Oilfield, Alaska, in 1984. From 19 June to 17 August, the radio transmitted 18 hours per day. A total of 346 locations were recorded, for a mean of 5.8 locations per day or one location every 3.1 hours of transmission time. The location of 13 direct observations of the radio-collared cow averaged less than 1 km from the nearest satellite-fixed location. The satellite-fixed locations of the radio-collared cow provided detailed data on movement patterns during the three seasons studied. The cow traveled an average of 8 km day1, 23 km1, and 14 km day1 during the post-calving season, mosquito season, and oestrid fly season, respectively.